THE IMPORTANCE OF MATHEMATICS IN PRODUCTION - Sheraliev Sadulla Suyunboevich; Djabbarov Odil Djuraevich (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This paper explores the significant role of mathematics in production processes. It highlights how mathematical methods such as optimization, statistical quality control, and simulation contribute to improving efficiency, reducing costs, and enhancing product quality. The study combines theoretical analysis with empirical data to demonstrate the practical benefits of applying mathematical tools in manufacturing. The findings underscore the necessity of integrating mathematics in modern production systems to achieve sustainable development and competitive advantage.